2019
DOI: 10.48550/arxiv.1911.06982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

VLUC: An Empirical Benchmark for Video-Like Urban Computing on Citywide Crowd and Traffic Prediction

Abstract: Nowadays, massive urban human mobility data are being generated from mobile phones, car navigation systems, and tra c sensors. Predicting the density and ow of the crowd or tra c at a citywide level becomes possible by using the big data and cu ing-edge AI technologies. It has been a very signi cant research topic with high social impact, which can be widely applied to emergency management, tra c regulation, and urban planning. In particular, by meshing a large urban area to a number of ne-grained mesh-grids, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…As shown in Figure 4, this spatio-temporal attention module is further divided into two sub-modules, a spatial attention 3D convolution. More works [10,41,42] have shown that a stack of 2D convolutions can effectively model nearby spatial dependencies, as well as distant spatial dependencies, in traffic data. However, 2D convolutions lack the ability to capture the temporal dependencies in multiple traffic congestion matrices.…”
Section: Sta Modulementioning
confidence: 99%
“…As shown in Figure 4, this spatio-temporal attention module is further divided into two sub-modules, a spatial attention 3D convolution. More works [10,41,42] have shown that a stack of 2D convolutions can effectively model nearby spatial dependencies, as well as distant spatial dependencies, in traffic data. However, 2D convolutions lack the ability to capture the temporal dependencies in multiple traffic congestion matrices.…”
Section: Sta Modulementioning
confidence: 99%
“…Many studies have been conducted to apply CNNs to capture the spatial features of traffic networks [10], [11]. CNN-based models are suitable for solving the problems that involve modeling the Euclidean correlations among different regions [12], [13]. These studies converted traffic networks to regular grids because the CNNs can only process Euclideanstructured data.…”
Section: A Gdl In Transportationmentioning
confidence: 99%
“…Many studies have proposed different methods for the task of crowd prediction, such as DCRNN [ 28 ], SRCNs [ 29 ], and multitask-net [ 30 ]. VLUC [ 31 ], PCRN [ 32 ], and PDB-ConvLSTM [ 33 ] use CNNs to process recent, near, and far data, respectively, and treat each timestamp as the equivalent convolution channel. STGCN [ 17 ], MRGCN [ 34 ], and ST-MGCN [ 34 ] fit a graph to the road structure and use convolution to learn temporal correlations.…”
Section: Related Workmentioning
confidence: 99%